Leading with character 10 minutes a day to a brilliant legacy - Loehr, Jim; Kenney, Caren (Recorded Books, 2020)
At the end of your life, how are you likely to be remembered? Chances are that people won't be praising your money, power, and status. Instead, the people you've impacted will remember you for your compassion and personal strength?in short, your character. Unfortunately, many leaders are unaware of their character shortcomings and blind spots that hold so many of us back from building the lasting legacy we are capable of. With the right motivation, you can begin to strengthen your character and become a moral and ethical leader capable of creating lasting change. In Leading with Character: 10 Minutes a Day to a Brilliant Legacy, Dr. Jim Loehr, cofounder of the Johnson & Johnson Human Performance Institute, reveals 50 character competencies that you can practice daily to transform your life and work. This book will also guide you through the process of developing a Personal Credo that will serve as your decision-making mission statement. Most leaders never take the time to identify their own core values, instead defaulting to a reflexive form of decision making. Gain an awareness of the conscious and unconscious processes that guide what you do and why you do it, and take charge of your leadership legacy. Even good leaders are vulnerable to corruption. Read Leading with Character to learn how human evolution and contemporary culture can lead us astray without our even knowing it. As we work hard to get to the top, who are we becoming along the way? If we want to become heroes whose memories will long outlast us, we need to channel our energy into creating habits that will add up to a strong and meaningful character.